2018
DOI: 10.1038/s41556-018-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt2 mediates intergenerational transmission of paternally acquired metabolic disorders through sperm small non-coding RNAs

Abstract: Summary The discovery of RNAs (e.g. mRNAs, non-coding RNAs) in sperm has opened the possibility that sperm may function in delivering additional paternal information aside from solely providing the DNA1. Increasing evidence now suggests that sperm small non-coding RNAs (sncRNAs) can mediate intergenerational transmission of paternally acquired phenotypes, including mental stress2, 3 and metabolic disorders4–6. How sperm sncRNAs encode paternal information remains unclear, but the mechanism may involve RNA modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
383
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(415 citation statements)
references
References 42 publications
(74 reference statements)
13
383
0
Order By: Relevance
“…Followup work showed that DNMT2 was responsible for these modifications. In contrast to wild-type animals, DNMT2 knockout mice failed to demonstrate a relative enrichment of m 5 C or m 2 G in the tRNA fragments after HFD [139]. The DNMT2 knockout mice fed a HFD did still produce tRNA fragments; in fact, they produced higher levels of tRNA fragments in agreement with previously reported data on DNMT2-mediated regulation of tRNA cleavage [103].…”
Section: Constitutive Trna Fragmentssupporting
confidence: 89%
“…Followup work showed that DNMT2 was responsible for these modifications. In contrast to wild-type animals, DNMT2 knockout mice failed to demonstrate a relative enrichment of m 5 C or m 2 G in the tRNA fragments after HFD [139]. The DNMT2 knockout mice fed a HFD did still produce tRNA fragments; in fact, they produced higher levels of tRNA fragments in agreement with previously reported data on DNMT2-mediated regulation of tRNA cleavage [103].…”
Section: Constitutive Trna Fragmentssupporting
confidence: 89%
“…In rodents, the triggering by high-fat diet of the metabolic disorder underlying obesity and diabetes is transmitted to offspring even if the latter eat healthy food. This transmission occurs through the transmission of small non-coding RNAs (sncRNAs) carried by sperm cells (Chen et al, 2016a;Zhang et al, 2018;review in Chen et al, 2016b). These RNAs are likely acquired by sperm cells during sperm transit in the epididymis (Sharma et al, 2016) in an intriguing form of soma to germen communication.…”
Section: Inheritance Of Acquired Disordersmentioning
confidence: 99%
“…These epididymis-synthesized sncRNAs, including miRNAs, tsRNAs, and perhaps the rsRNA-28S, are therefore delivered to the zygote as vital epigenetic information and involved in the regulation of certain early embryonic events and even have profound consequence to the development of the offspring (Chen et al, 2016a;Sharma et al, 2016;Zhang et al, 2018). These epididymis-synthesized sncRNAs, including miRNAs, tsRNAs, and perhaps the rsRNA-28S, are therefore delivered to the zygote as vital epigenetic information and involved in the regulation of certain early embryonic events and even have profound consequence to the development of the offspring (Chen et al, 2016a;Sharma et al, 2016;Zhang et al, 2018).…”
Section: Progress Over the Past Decadementioning
confidence: 99%
“…Some other sncRNA containing epididymosomes transfer their cargos to the passing spermatozoa. These epididymis-synthesized sncRNAs, including miRNAs, tsRNAs, and perhaps the rsRNA-28S, are therefore delivered to the zygote as vital epigenetic information and involved in the regulation of certain early embryonic events and even have profound consequence to the development of the offspring (Chen et al, 2016a;Sharma et al, 2016;Zhang et al, 2018). The biological significance for the spermatozoa to obtain these sncRNAs during epididymal transit was further emphasized by the study showing that embryos generated using mouse caput epididymal spermatozoa tended to fail soon after implantation, and the microinjection of purified cauda-specific sncRNAs into these embryos can rescue this lethality phenotype .…”
Section: Extensive Functions Of the Epididymal Sncrnas: From In Situ mentioning
confidence: 99%